2018
DOI: 10.1520/ssms20180019
|View full text |Cite
|
Sign up to set email alerts
|

A Data Processing Pipeline for Prediction of Milling Machine Tool Condition from Raw Sensor Data

Abstract: With recent advances in sensor and computing technology, it is now possible to use real-time machine learning techniques to monitor the state of manufacturing machines. However, making accurate predictions from raw sensor data is still a difficult challenge. In this work, a data processing pipeline is developed to predict the condition of a milling machine tool using raw sensor data. Acceleration and audio time series sensor data is aggregated into blocks that correspond to the individual cutting operations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In their study, Gaussian process regression, which is a non-parametric ML approach, was used for optimization. Ferguson et al (2018) suggested that at present, it is possible to use real-time ML approaches to monitor the current state of machines. ML techniques are capable to handle large datasets that are complex in nature.…”
Section: Review Methodologymentioning
confidence: 99%
“…In their study, Gaussian process regression, which is a non-parametric ML approach, was used for optimization. Ferguson et al (2018) suggested that at present, it is possible to use real-time ML approaches to monitor the current state of machines. ML techniques are capable to handle large datasets that are complex in nature.…”
Section: Review Methodologymentioning
confidence: 99%